2016
DOI: 10.1016/j.ophtha.2016.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Pressure Reduction after Phacoemulsification versus Manual Small-Incision Cataract Surgery

Abstract: Both phacoemulsification and MSICS led to significant and similar IOP reductions 6 months after surgery, and both surgeries produced similar changes in anterior chamber and angle parameters. Higher baseline IOP was associated with greater IOP reduction; IOP reduction also can be attributed partly to changes in angle and anterior chamber configuration, although these parameters were unable to predict significantly predict IOP drop at 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
17
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 29 publications
6
17
1
2
Order By: Relevance
“…Mean IOP at 6 weeks and 3 months in all 3 study groups was found to be lower than pre-operative IOP. The relatively lower mean IOP at 3 months observed in this study was in keeping with results from previous studies [ 7 , 12 , 16 ], and this further corroborates the fact that cataract surgery plays a role in increasing aqueous outflow facility in patients with open angles, as well as widens and deepens the AC angle in eyes with narrow angles as reported by previous studies [ 18 , 19 ]. Some factors other than the type of cataract surgery performed, such as the degree of inflammation, steroid responsiveness among others, could influence IOP changes following cataract surgery.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Mean IOP at 6 weeks and 3 months in all 3 study groups was found to be lower than pre-operative IOP. The relatively lower mean IOP at 3 months observed in this study was in keeping with results from previous studies [ 7 , 12 , 16 ], and this further corroborates the fact that cataract surgery plays a role in increasing aqueous outflow facility in patients with open angles, as well as widens and deepens the AC angle in eyes with narrow angles as reported by previous studies [ 18 , 19 ]. Some factors other than the type of cataract surgery performed, such as the degree of inflammation, steroid responsiveness among others, could influence IOP changes following cataract surgery.…”
Section: Discussionsupporting
confidence: 93%
“…The steady decline in IOP observed in all 3 groups from 1 st day to 1 st week post-operative period may have been due to resolution of inflammation following post-operative steroid use and clearance of remnant viscoelastic material from the AC. Like in previous studies, patients who had phacoemulsification in this study had a decline in IOP from 1 st week to 3 rd week post-operative period [ 11 , 16 ]. On the other hand, IOP was found to increase in both ECCE and MSICS groups contrary to findings in other studies [ 7 , 16 ].…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations